Histopathological effects resulting from infection stray cats by intestinal parasites in Saladin province - Ashraf Jamal Mahmoud Zangana (Tikrit Journal of Pure Science, 2023)
In this, study89stray cats were examined in Saladin province, of both sexes and various ages, which included 82 stray cats and 7 cats as a group control. Showed the infected cats number" of clinical examination and  stood infection rate of intestinal parasites 41.46%, was diagnosed with worms Toxocara cati by 8.53%, Toxascaris leonine by 13.41%, and Taenia spp. by 31.70%, and Dipylidium caninum by 15.85%, and Diphyllobothrium sp. by 7.31% and eggs bags each of Isospora spp. by 20.73%, and Giardia spp. 6.09%  and Toxoplasma gondii by 10.97%.  Histopathological examination of  the intestines, showed degeneration of columnar epithelial cells and necrosis of some of them and also alienations, the villi in the intestinal cavity, with the presence of large numbers of inflammatory white blood cells within the core of the villi, and the muscular wall of the intestines contained inflammatory cells severe macular disintegration with severe degeneration in many fiber other muscle, as large vacuole appeared in the cytoplasm of the muscle fibers.